Incidence and distribution of jaw pathologies among 0-15 years age group at a tertiary rural health-care center of Maharashtra: A retrospective study of 10 years - Parul Tandon; Seemit Shah; Anuj Dadhich; Harish Saluja; Himanshu Chauhan (Wolters Kluwer Medknow Publications, 2020)
Objective: This study was undertaken to investigate the prevalence of intraosseous jaw lesions among pediatrics (0-15 years of age) in a rural health-care center of Maharashtra and to determine the most common types of lesions and their distribution according to gender and anatomical site involved. Study Design: Histopathological data were collected from a database of lesions classified as intraosseous jaw lesions dated between January 1, 2005, and December 31, 2015, from the archives of the Department of Oral and Maxillofacial Surgery, Rural Dental College, Maharashtra, India. All the cases of jaw cysts and tumors among children under 16 years of age group were segregated and scrutinized further under the headings of type of pathologies, anatomical locations where they are most commonly seen, and the age/gender most pertinent to these pathologies. Results: The present study revealed that 114/3896 jaw lesions were pediatric jaw pathologies, of which odontogenic cysts were 67/114 and jaw tumors were 47/114. Among the cysts, 70% were developmental cysts and 30% were inflammatory cysts. The majority (71.6%) of the jaw cysts were found in the mixed dentition phase (7-15 years). Among the jaw tumors, 55% of them were categorized under odontogenic tumors and 45% were under fibro-osseous lesions. Similar to intraosseous jaw cysts, tumors of jaws were more prevalent under the age of mixed dentition, which was found to be 87%. Male predominance was seen and the overall male:female ratio was calculated as 1:0.52 and 1:0.5 for cysts and tumors, respectively. Mandibular posterior segment was found to be the most commonly encountered anatomical site in both the groups of cases. Conclusion: A large number of cases were recorded, which led us to a path of interrogation through which the reason for increased incidence was extracted, and it was agreed that though the pathogenesis remains the same in every individual, routine health checkups and early diagnosis may reduce the incidence and aggressiveness of pathologies, respectively, which was lacking at the rural area.